2016
DOI: 10.3847/0004-637x/825/2/145
|View full text |Cite
|
Sign up to set email alerts
|

Hubble Space Telescope Observations of Accretion-Induced Star Formation in the Tadpole Galaxy Kiso 5639

Abstract: The tadpole galaxy Kiso 5639 has a slowly rotating disk with a drop in metallicity at its star-forming head, suggesting that star formation was triggered by the accretion of metal-poor gas. We present multi-wavelength Hubble Space Telescope Wide Field Camera 3 images of UV through I band plus Hα to search for peripheral emission and determine the properties of various regions. The head has a mass in young stars of~ M 10 6 and an ionization rate of6.4 10 51 s −1 , equivalent to ∼2100 O9-type stars. There are f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 67 publications
1
18
0
Order By: Relevance
“…Sánchez Almeida et al (2015) found low-metallicity starburst regions in nine out of ten extremely-metal poor galaxies. Elmegreen et al (2016) reported a drop in metallicity at the star-forming head in the tadpole galaxy Kiso 5639. All these previous works interpret their finding of metallicity drops in the star-forming regions as a result of accretion of metal-poor gas.…”
Section: Discussion: Possibility Of Chemical Inhomogeneitiesmentioning
confidence: 99%
“…Sánchez Almeida et al (2015) found low-metallicity starburst regions in nine out of ten extremely-metal poor galaxies. Elmegreen et al (2016) reported a drop in metallicity at the star-forming head in the tadpole galaxy Kiso 5639. All these previous works interpret their finding of metallicity drops in the star-forming regions as a result of accretion of metal-poor gas.…”
Section: Discussion: Possibility Of Chemical Inhomogeneitiesmentioning
confidence: 99%
“…In addition to having chemically primitive starforming regions, XMPs also show signs of being structurally primitive, as if they were disks in early stages of assembly, with massive off-center starbursts providing them with a characteristic tadpole shape (e.g., Papaderos et al 2008;Morales-Luis et al 2011;Elmegreen et al 2012bElmegreen et al , 2016, with slowly rotating bodies, and with large spatially-unresolved turbulent motions (e.g., Sánchez Amorín et al 2015).…”
mentioning
confidence: 99%
“…Furthermore, at least one tadpole head has been found to have a much higher SFR for its probable gas density (Elmegreen et al 2016b), similar to the HSF region in NGC 3738 as shown in Figure 5. Measurements of the oxygen abundance in several tadpoles revealed that the heads are more metal-poor than the bodies (Sánchez Almeida et al 2014;Elmegreen et al 2016b), and this characteristic of the tadpoles suggests the possibility that the star-forming head is the result of infall of metal-poor gas (Elmegreen et al 2016b;Ceverino et al 2016). On the other hand, the oxygen abundances of DDO 187 and NGC 3738 are fairly high (see Table 1), which would be inconsistent with accretion of metal-poor gas from the cosmic web.…”
Section: Discussionmentioning
confidence: 63%
“…However, local tadpoles have been found that are comparable to DDO 187 and NGC 3738, and this morphology is relatively common among extremely metal-poor galaxies (Morales-Luis et al 2011). Furthermore, at least one tadpole head has been found to have a much higher SFR for its probable gas density (Elmegreen et al 2016b), similar to the HSF region in NGC 3738 as shown in Figure 5. Measurements of the oxygen abundance in several tadpoles revealed that the heads are more metal-poor than the bodies (Sánchez Almeida et al 2014;Elmegreen et al 2016b), and this characteristic of the tadpoles suggests the possibility that the star-forming head is the result of infall of metal-poor gas (Elmegreen et al 2016b;Ceverino et al 2016).…”
Section: Discussionmentioning
confidence: 87%